The Therapeutic potential of farm dust extracts in a mouse model of eosinophilic inflammation - Korkmaz, Rabia Ülkü; Omony, Jimmy; Tan, Xiaomei; Klotz, Markus; Dragunas, Guilherme; Chen, Sirui; Shankhwar, Soni; Ertuz, Zeynep; Mueller, Christoph; Ragab, Mohab; Jeridi, Aicha; Augustin, Romina; et al. (Allergy, 2025)
Background Asthma affects over 355 million people globally and poses a major healthcare burden. While corticosteroids remain a cornerstone of treatment, their side effects highlight the need for additional therapeutic strategies. Environmental exposures such as traditional farm dust have been linked to protection against asthma and allergies. This study investigated the therapeutic potential of farm dust extract (FDE) in a murine model of allergic asthma when administered after sensitization and during allergen challenge, mimicking a secondary prevention or early interventional treatment approach.Methods We used an ovalbumin (OVA)-induced asthma model to evaluate FDE effects on airway eosinophilia, airway hyperresponsiveness (AHR), mucus production, and IgE levels. Mechanistic studies assessed regulatory T cells (Tregs), dendritic cell phenotype, epithelial barrier integrity, and cytokine signaling. Complementary experiments were performed in peripheral blood mononuclear cells (PBMCs) from asthmatic donors.Results FDE significantly reduced airway inflammation and AHR, with secondary prevention effects comparable to systemic dexamethasone. FDE enhanced Treg frequency and CTLA-4 expression, modulated dendritic cell MHC-II and PD-L1 expression, and promoted an immunoregulatory environment. It also restored epithelial barrier integrity and increased IL-33 release, supporting Treg activation. In asthmatic PBMCs, FDE increased Tregs, reduced Th2 cells, and suppressed CIITA, suggesting similar immune-regulatory effects. Interactions among IL-33, amphiregulin (AREG), and Tregs highlighted a mechanism reinforcing immune-epithelial homeostasis.Conclusion FDE administered after sensitization and during allergen challenge mitigated key asthma features in mice and showed translational potential in human cells, supporting its development as a novel, environmentally derived immunomodulatory strategy.
Gesehen am 27.02.2026